Climate Justice: Challenges and Future Strategies for Courts on Climate Change in Indonesia - Nikmah Fitriah; Indriati Amarini (Universitas Muhammadiyah Purwokerto, 2025)
Climate change has become a global phenomenon characterized by an increase in the earth's average temperature, which is largely caused by human activities. The use of Litigation to resolve climate change issues has more than doubled since 2017 and is still growing. This research aims to explore the challenges and strategies in mainstreaming climate justice in Indonesia through climate change courts. With a doctrinal approach, this research will examine primary legal sources, such as legislation, jurisprudence, and international documents, as well as secondary sources, such as academic literature and organizational reports, to produce evidence-based recommendations for the development of a legal framework for climate justice in Indonesia. The research results show that climate change makes courts an important player in multi-level climate governance, therefore courts must have climate sensitivity and awareness. There is a need for specific material and procedural laws regarding climate and the need to develop the knowledge and skills of judges.